EFEKTIVITAS MUSYAWARAH PERENCANAAN PEMBANGUNAN DI WILAYAH PEDALAMAN DISTRIK SUATOR KABUPATEN ASMAT PROVINSI PAPUA SELATAN - Tiau, Bakau (Jurnal Wahana Bina Pemerintahan, 2023)
Currently, Musrembang in the Suator District from the villages is often late and for this reason researchers want to know the effectiveness of development planning deliberations in the interior of the Suator District, Asmat Regency, the supporting and inhibiting factors and the efforts made. This research was carried out as one of the requirements for students in the government science master's program to prepare which is supported by several theories, namely government theory, effectiveness theory, planning theory, participatory theory, and development theory with a qualitative approach. The research results serve as information for researchers for further research, academically as reference material for the regional government of Asmat Regency and Suator District, input in outlining policies to increase the effectiveness of Musrembang in the interior of Suator District. The conclusion is that the village musrembang has not been effective, which shows that the pre-musrembang stage of the village, the implementation stage of the village musrembang, and the post-musrembang stage of the village have not complied with statutory regulations both internally and externally. Supporting factors, namely awareness and willingness, ability and opportunity, kinship and kinship, level of education. The inhibiting factors are knowledge, skills, attitudes and socialization that do not reach the community. The efforts made are to implement the mandate of five approaches in regional development, namely making political approaches more effective, increasing community participation more effective, empowering technocratic personnel, making bottom-up systems (from the bottom up) and top down systems (from top to bottom) more effective. It is recommended for local governments to create a planning stage as a guideline for implementing the participatory planning planning process, outreach to district officials and communities to supervisors. Together with the community, traditional leaders, village heads/NGOs, they always monitor the results of participatory development planning at the village and district levels so that proposed activities attention is brought to the district level.